Mediators of the effect of nicotine pre‐treatment on quitting smoking. (16th September 2018) - Hajek, Peter; Lewis, Sarah; Munafo, Marcus; Lindson, Nicola; Coleman, Tim; Aveyard, Paul; ,
Abstract: Background and aims: Using smoking cessation medications for several weeks prior to quitting smoking facilitates quitting success, but how it does so is not clear. Candidate theories are that pre‐cessation medication enhances self‐efficacy, facilitates medication adherence post‐quit, induces aversion to smoking, reduces reward from smoking or reduces the drive to smoke. We investigated these pathways using data from a large trial of nicotine pre‐loading, using mediation analysis. Design: Randomized controlled trial of nicotine pre‐loading. Potential mediators were assessed at baseline and 1 week into the pre‐loading (3 weeks prior to quitting). In addition to this, urges to smoke in abstainers were assessed 1 week after the target quit date. Setting: England. Participants: A total of 1792 smokers who wanted to quit attending specialist smoking cessation services in England were enrolled between 13 August 2012 and 10 March 2015. Intervention and comparator: Participants were randomized to either standard smoking cessation medications accompanied by behavioural support or the same treatment supplemented by nicotine 'pre‐loading', i.e. 4 weeks of 21 mg nicotine patch use prior to quitting. Measurements: The primary outcome, selected for its proximity in time to potential mediators, was biochemically validated abstinence from smoking at 4 weeks post‐target quit date. Potential mediators included the Modified Cigarette Evaluation Questionnaire, with subscales assessing satisfaction, reward, craving and aversion; ratings of strength and frequency of urges to smoke; the Mood and Physical Symptoms Scale assessing cigarette withdrawal symptoms; two items from the Nicotine Dependence Syndrome Scale assessing smoking stereotypy; self‐reported reduction in cigarettes per day and in carbon monoxide (CO) reading; post‐target quit day (TQD) medication adherence; self‐efficacy; nausea. Findings: Pre‐loading reduced urges to smoke at 3 weeks pre‐quit ( P  < 0.001) and exhaled CO concentrations ( P  < 0.001), and also urges to smoke post‐quit in abstainers ( P  = 0.001). At 3 weeks pre‐quit, it also reduced cigarette consumption, enjoyment of and satisfaction from smoking and smoking reward and increased nausea, aversion (all P  < 0.001) and smoking stereotypy ( P  = 0.003). Only the first three variables, however (reduced smoke intake and reduced urges to smoke pre‐ and post‐quit), mediated abstinence from smoking at 4 weeks and only the latter two mediated abstinence at 6 months (indirect mediating effects P  < 0.05). Conclusions: Nicotine pre‐loading appears to facilitate smoking abstinence by reducing urges to smoke and smoke intake before quitting and urges to smoke after quitting.